Performance comparison of LaB6 and C12A7:e-emitters for space electric propulsion cathodes. Issue 1 (1st February 2022) - Toledo, J.; Plaza, J F; Post, A; Zschätzsch, D; Reitemeyer, M; Chen, L; Gurciullo, A; Siegl, A; Klar, P J; Lascombes, P.; Seifert, B.
Abstract: This work, based on an EU-funded project, NEMESIS, is aiming at developing electride-based cathode technology which is compatible with all kinds of electric propulsion systems requiring neutralization. Its target is to demonstrate and validate the performance of a novel C12A7:e-electride material as electron emitter instead of traditional thermionic emitters such as lanthanum hexaboride, LaBe, or barium oxide, BaO. In this study, a fair comparison between LaBe and C12A7:e-samples was performed both addressing pure material characterization parameters as well as comparing performance as cathodes under different architectures and operational conditions. In this case, a current/cathode power ratio around 3 mA/W was obtained when using the C12A7:e-sample in a plasma environment with Ar, which is approximately one order of magnitude higher compared to the LaB6 sample.